Dropshipping and Reselling Studies in Muamalat Fiqh - Aang Asari; Ni’mah Zaidah (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2022)
Abstract: The practice of Dropshipping & reselling, is a new concept in Islamic law. Dropshipping is a product sale that allows sellers to sell their products to customers with an image based on the owner of the goods (supplier) without having to stock up on goods and sell to customers at a specified price. So, in this case the seller is an active actor to find customers. Meanwhile, reselling is a term that is also used to describe a marketing or sales system for a product that involves three parties, namely the owner of the goods, the buyer and the reseller. This type of research uses a literature study approach, using a qualitative narrative method. The results of this study can show that buying and selling with a dropship and reseller system does not violate sharia provisions. Even though the parties do not have the goods and the capital is only the specifications, Islamic law allows this kind of contract. The contract can be as a simsarah or broker, it can also be a salam contract (order). However, if it is planned with a salam contract, it must fulfill several conditions, among others: what is sold is not the other but the specifications, the goods are not delivered at the time of the contract, there is a time limit for the delivery of the goods and the place of delivery of the goods is clear.Abstrak: Praktik Dropshipping & reselling, adalah konsep baru dalam hukum Islam. Dropshipping merupakan penjualan produk yang memungkinkan penjual menjualkan produknya pada pelanggan bermodalkan gambar berdasarkan pemilik barang (supplier) tanpa wajib menyetok barang & menjual ke pelanggan menggunakan harga yg ditentukan. jadi, pada hal ini penjual merupakan pelaku aktif buat mencari pelanggan. Sedangkan reselling adalah istilah yang juga digunakan untuk menyebutkan salah satu sistem pemasaran atau penjualan suatu produk yang melibatkan tiga pihak, yaitu pemilik barang, pembeli dan reseller. Jenis penelitian ini memakai pendekatan studi literatur pustaka, memakai metode naratif kualitatif. Hasil kajian ini dapat menunjukan bahwasannya, jual beli dengan sistem dropship dan reseller tidak melanggar ketentuan syariah. Meski para pihak belum memiliki barangnya dan modal hanya baru spesifikasinya saja. Syariat Islam membolehkan akad seperti ini. Namun sekema akadnya bisa saja sebagai simsarah atau broker, bisa juga akad salam (pesanan). Namun jika itu diskemakan dengan akad salam, harus memenuhi beberapa syarat, antara lain: yang dijual bukan ainnya akan tetapi spesifikasinya saja, barang tidak diserahkan pada saat akad, ada batas waktu penyerahan barang dan jelas tempat penyerahan barangnya.